Planned home birth: promoting safe home birth and midwifery model of care in Sokoto Nigeria - Muhammad, Auwalu; Lee, Khuan; Shariff Ghazali, Sazlina; Hassan, Mairo; Md Said, Salmiah (Universiti Putra Malaysia Press, 2020)
This book provides details on what constitutes an ideal planned home birth practice among midwives and maternity providers—during antenatal, intrapartum, and postpartum. One unique feature of this book is that we included clinical vignettes in each session to facilitate active learning and experience sharing regarding planned home birth practice among midwives. We believe that this book will be useful to midwives, maternity care providers, and educators in teaching the planned home birth practice.